NUMERICAL CRITERIA OF THE VARIABILITY OF THE INDIVIDUAL PULSATING CYCLES IN THE LPVs - Marsakova, V. I. (Одеські астрономічні публікації, 2017)
Some numerical parameters of long term changes of light curves in LPVs are obtained. Results of analysis of the sample of 53 LPVs and classification of these stars are discussed.